Longitudinal Changes in Magnetic Resonance Spectroscopy in Pediatric Concussion: A Pilot Study - Meyer, Erin J.; Stout, Jeffrey N.; Chung, Ai Wern; Grant, P. Ellen; Mannix, Rebekah; Gagoski, Borjan (Frontiers in Neurology, 2019)
Background: Nearly 20% of US adolescents report at least one lifetime concussion. Pathophysiologic models suggest that traumatic biomechanical forces caused by rotational deceleration lead to shear stress, which triggers a neurometabolic cascade beginning with excitotoxicity and leading to significant energy demands and a period of metabolic crisis for the injured brain. Proton magnetic resonance spectroscopy (1H MRS) offers a means for non-invasive measurement of neurometabolic changes after concussion. Objective: Describe longitudinal changes in metabolites measured in vivo in the brains of adolescent patients with concussion. Methods: We prospectively recruited nine patients ages 11 to 20 who presented to a pediatric Emergency Department within 24 hours of concussion. Patients underwent MRI scanning within 72 hours (acute, n = 8), two weeks (subacute, n = 7), and at approximately one year (chronic, n = 7). Healthy, age and sex-matched controls were recruited and scanned once (n = 9). 1H MRS was used to measure N-acetyl-aspartate, choline, creatine, glutamate+glutamine, and myo-inositol concentrations in six regions of interest: left and right frontal white matter, posterior white matter and thalamus. Results: There was a significant increase in total thalamus glutamate+glutamine/choline at the subacute (p = .010) and chronic (p = .010) time points, and a significant decrease in total white matter myo-inositol/choline (p = .030) at the chronic time point as compared to controls. Conclusion: There are no differences in 1H MRS measurements in the acute concussive period; however, changes in glutamate+glutamine and myo-inositol concentrations detectable by 1H-MRS may develop beyond the acute period.